Effect of Absorptive Capacity on Strategic Flexibility and Supply Chain Agility: Implications for Performance in Fast-Moving Consumer Goods - Jabarzadeh, Younis; Khangah, Mahdiyar Hosseinkhanli; cemberci, Murat; Cerchione, Roberto; Sanoubar, Naser (OSCM FORUM, 2022)
This paper develops a model to examine the relationships between absorptive capacity (ACAP), strategic flexibility (SF), supply chain agility (SCA), and firm performance (FP) based on the resource-based view (RBV) and the dynamic capabilities view (DCV). Using structured questionnaire, a sample of 186 randomly selected firms in fast-moving consumer goods (FMCG) industry from both Turkey and Iran as two developing countries is used to test the hypotheses. Variance-based structural equation modeling (SEM) was the primary data analysis method. The results show that absorptive capacity has direct and indirect effects on performance with the mediator variables of supply chain agility and strategic flexibility. Moreover, increased absorptive capacity leads to increased supply chain agility that in turn improves performance. The effect of absorptive capacity on strategic flexibility, and also, the overall proposed conceptual model, especially in the FMCG industry are the original features of the current study which was conducted in two developing countries. Efforts to promote absorptive capacity can improve both strategic flexibility and supply chain agility which are effective factors for enhancing performance in the fast-changing environment of FMCG industry.
Keywords: Strategic flexibility; supply chain agility; absorptive capacity; firm performance; fast-moving consumer goods; HIGH-TECHNOLOGY; ENABLING ROLE; KNOWLEDGE; CAPABILITIES; INNOVATION; IMPACT; CONCEPTUALIZATION; ORIENTATION; INTEGRATION; Business & Economics